PEMANFAATAN INTERNET CONNECTION SHARING - Ahmad Louis (JURNAL AKADEMIKA)
Internet Connection Sharing (ICS) is the use of a device with Internet access such as 3G cellular service, broadband via Ethernet, or other Internet gateway as an access point for other devices. It was implemented by Microsoft as a feature of its Windows operating system for sharing a single Internet connection on one computer between other computers on the same local area network. Connection to the Internet through an ISP (Internet Service Provider) can be done in several ways depending on the funds available and their use, such as connecting to the Internet only for e-mail, browsing, downloading can take advantage of dial-up with a phone line. But if the network is used for broader purposes, could use lised line. However Internnet connection to the system essentially is divided into two main types, namely using a telephone connection and broadband connection